A history of Western music - Grout, Donald Jay (Norton, 2001)
Recognized as the finest survey of Western art music in the English language, this distinguished book has enlightened a multitude of music lovers since it first appeared in 1960. This handsome new edition incorporates the latest advances in music scholarship.